Protein Aggregation Profile of the Bacterial Cytosol - de Groot, Natalia S.; Ventura, Salvador (PloS one, 2010)
Protein misfolding is usually deleterious for the cell, either as a consequence of the loss of protein function or the buildup of insoluble and toxic aggregates. The aggregation behavior of a given polypeptide is strongly influenced by the intrinsic properties encoded in its sequence. This has allowed the development of effective computational methods to predict protein aggregation propensity. Here, we use the AGGRESCAN algorithm to approximate the aggregation profile of an experimental cytosolic Escherichia coli proteome. The analysis indicates that the aggregation propensity of bacterial proteins is associated with their length, conformation, location, function, and abundance. The data are consistent with the predictions of other algorithms on different theoretical proteomes. Overall, the study suggests that the avoidance of protein aggregation in functional environments acts as a strong evolutionary constraint on polypeptide sequences in both prokaryotic and eukaryotic organisms.